A novel signature based on pyroptosis-related genes for predicting prognosis and treatment response in prostate cancer patients - Xiao, Xi; Li, Jianpeng; Wan, Shun; Wu, Mingzhe; Li, Zonglin; Tian, Junqiang; Mi, Jun (Frontiers in Genetics, 2022)
Background: Pyroptosis is a form of programmed cell death, accompanied by the release of inflammatory factors and immune responses, and is closely related to the occurrence and progression of various cancers. However, the relationships between pyroptosis-related genes (PRGs) and disease prognosis, tumor microenvironment (TME), and drug treatment effects in prostate cancer (PCa) are unclear. Methods: We obtained the differentially expressed PRGs in PCa tissues and normal prostate tissues based on the Cancer Genome Atlas database (TCGA). On this light, the univariate, LASSO, and multivariate Cox regression analysis were used to obtain prognostic hub genes. Meanwhile, qRT-PCR was used to validate the expression of hub genes between PCa lines and normal prostate epithelial cell lines. We then constructed and validated a risk model associated with the patient’s disease-free survival (DFS). Finally, the relationships between risk score and clinicopathological characteristics, tumor immune microenvironment, and drug treatment response of PCa were systematically analyzed. Results: A prognostic risk model was constructed with 6 hub PRGs (CHMP4C, GSDMB, NOD2, PLCG1, CYCS, GPX4), and patients were divided into high and low-risk groups by median risk score. The risk score was confirmed to be an independent prognostic factor for PCa in both the training and validation sets. Patients in the high-risk group had a worse prognosis than those in the low-risk group, and they had more increased somatic mutations, higher immune cell infiltration and higher expression of immune checkpoint-related genes. Moreover, they were more sensitive to cell cycle-related chemotherapeutic agents and might be more responsive to immunotherapy. Conclusions: In our study, pyroptosis played a significant function in the prognosis of PCa and the management of the tumor microenvironment. Meanwhile, evaluating the patient's response to immunotherapy and chemotherapy might help to develop more effective individual treatment strategies.